Maps that preserve higher-dimensional numerical ranges with operator Jordan products. Issue 12 (2nd December 2017) - Chen, Chaoqun; Lu, Fangyan
Abstract : Let k be a positive integer. Let H and K be complex Hilbert spaces with dimension greater than k . In this paper, we characterize the surjective maps from to that preserve the k -dimensional numerical ranges of Jordan products or Jordan -products of operators.